Mangngade Tradition Sustaining Social Cohesion and Collective Identity - Nur Aulia; Muhammad Syukur; A. Octamaya Tenri Awaru; Najamuddin Najamuddin (Academia Open, 2026)
General Background Local traditions represent accumulated cultural values that function as social frameworks within community life. Specific Background The Mangngade tradition in Mattampawalie Village, Bone Regency, persists as a hereditary cultural practice involving collective rituals, symbolic offerings, and communal participation rooted in local wisdom and acculturated religious values. Knowledge Gap Despite its continued practice, limited scholarly attention has explicitly positioned Mangngade as an active social mechanism that maintains social cohesion and collective identity amid modernization pressures. Aims This study aims to analyze the construction of the Mangngade tradition and examine its role in sustaining social cohesion and collective identity within the Mattampawalie Village community. Results Findings indicate that Mangngade functions beyond a spiritual ritual by internalizing core social values such as sipakatau, sipakalebbi, mutual cooperation, togetherness, and social responsibility through intensive intergenerational interaction and collective participation. These practices foster solidarity, trust, and harmonious social relations while reinforcing communal bonds. Novelty This research highlights Mangngade as a form of local wisdom that remains socially functional through adaptive practices, demonstrating its role as living social capital rather than a static ceremonial tradition. Implications The findings suggest that sustained synergy among customary leaders, village governance, and community members—particularly youth—supports the continuity of Mangngade as a cultural instrument that maintains social cohesion and collective identity in the context of ongoing social change. Highlights: Communal rituals internalize shared values that maintain solidarity and togetherness. Collective participation creates sustained intergenerational social interaction. Adaptive cultural practices preserve communal bonds amid social change. Keywords : Mangngade Tradition, Social Cohesion, Collective Identity, Local Wisdom, Community Participation